Surge in regulatory cells does not prevent onset of hyperglycemia in NOD mice. (March 2014) - Kaminitz, Ayelet; Mizrahi, Keren; Askenasy, Nadir
Abstract Immune profiling of non-obese diabetic (NOD) is a widely employed tool to assess the mechanisms of inflammatory insulitis. Our analysis of the female NOD colony revealed similar distribution of lymphoid lineages to wild type mice, and at various ages of prediabetic and diabetic mice. The profiles of mesenteric and pancreatic lymph nodes differ and often change reciprocally due to directed migration of T cells towards the site of inflammation. Significant events in our colony include early decline in CD4+CD25+CD62L+ Treg, accompanied by gradual increase in CD4+CD25+FoxP3+ Treg in peripheral lymphoid organs and pancreatic infiltrates. Impressively, aged euglycemic mice display significant transient rise in CD4+CD25-FoxP3+ Treg in the thymus, pancreas and draining lymph nodes. A significant difference was superior viability of effector and suppressor cells from new onset diabetics in the presence of high interleukin-2 (IL-2) concentrations in vitro as compared to cells of prediabetic mice. Overall, we found no correlation between FoxP3+ Treg in the pancreatic lymph nodes and the inflammatory scores of individual NOD mice. CD25-FoxP3+ Treg are markedly increased in the pancreatic infiltrates in late stages of inflammation, possibly an effort to counteract destructive insulitis. Considering extensive evidence that Treg in aged NOD mice are functionally sufficient, quantitative profiling evolves as an unreliable tool to assess mechanism and causes of inflammation under baseline conditions. Immune profiles are modulated by thymic output, cell migration, shedding of markers, proliferation, survival and in-situ evolution of regulatory cells.